2017
DOI: 10.1523/jneurosci.3390-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Spreading Depression Closes Paravascular Space and Impairs Glymphatic Flow: Implications for Migraine Headache

Abstract: Functioning of the glymphatic system, a network of paravascular tunnels through which cortical interstitial solutes are cleared from the brain, has recently been linked to sleep and traumatic brain injury, both of which can affect the progression of migraine. This led us to investigate the connection between migraine and the glymphatic system. Taking advantage of a novel in vivo method we developed using two-photon microscopy to visualize the paravascular space (PVS) in naive uninjected mice, we show that a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
196
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(211 citation statements)
references
References 92 publications
10
196
0
5
Order By: Relevance
“…CAA and CADASIL) characterized by protein aggregation and deposition. Glymphatic function has been assessed in several highly relevant processes to SVD including aging(28) and diseases such as microinfarction (29, 30), stroke (31), Alzheimer’s disease (AD)(32), migraine(33), and diabetes(34). Extrapolating from the current literature, we will focus on the effects that altered PVS structure and function, arterial pulsatility, and clearance have on glymphatic function.…”
Section: Glymphatic Systemmentioning
confidence: 99%
“…CAA and CADASIL) characterized by protein aggregation and deposition. Glymphatic function has been assessed in several highly relevant processes to SVD including aging(28) and diseases such as microinfarction (29, 30), stroke (31), Alzheimer’s disease (AD)(32), migraine(33), and diabetes(34). Extrapolating from the current literature, we will focus on the effects that altered PVS structure and function, arterial pulsatility, and clearance have on glymphatic function.…”
Section: Glymphatic Systemmentioning
confidence: 99%
“…First, Schain et al (2017) recently showed that SD induces transient closing of the paravascular spaces, impairing glymphatic flow. This transient closing of paravascular spaces would potentially impair IGF-1 access to areas of brain affected by the SD we induced immediately prior to intranasal administration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Just like Alzheimer's disease, glaucoma might be caused by an imbalance between the production and clearance of neurotoxins, including amyloid-β [24]. Schain et al argue that impairment of the glymphatic system can be involved in the pathogenesis of migraine [28]. Hitscherich et al consider the possibilities of so-called "osteopathic manipulative treatment" to improve the function of the glymphatic system.…”
Section: Arc Journal Of Neuroscience Page|19mentioning
confidence: 99%
“…Hitscherich et al consider the possibilities of so-called "osteopathic manipulative treatment" to improve the function of the glymphatic system. They note that these manipulations could concentrate on opening myofascial transition areas, maximalization of diaphragmatic movement and augmenting lymphaticovenous outflow [28].…”
Section: Arc Journal Of Neuroscience Page|19mentioning
confidence: 99%
See 1 more Smart Citation